THE USE OF THE WORLD WALL PICTURES MEDIA IN IMPROVING AUTISTIC STUDENTS’ VOCABULARY AT A MATARAM STATE SPECIAL SCHOOL - Nurul Suriyani; Yuni Budi Lestari; Atri Dewi Aziz (Journal of English Education Forum (JEEF), 2023)
Vocabulary is the first step that must be learned in learning English. Everyone has the right to get education without exception including autistic students. This study aims to describe teachers’ use of the word wall pictures in improving autistic students’ vocabulary. The population was all autistic teachers and the sample was two autistic teachers at a Mataram State Special School. Samples were taken by using Purposeful sampling. The research used a qualitative research method which implemented a case study approach. The study found that the teachers employed some techniques of using the word wall pictures media to improve autistic students' vocabulary. Brainstorming, model, listen and repeat, and practice are some techniques of using the word wall pictures media to improve autistic students' vocabulary. The study also revealed that the use of the word wall pictures media was effective in improving autistic students’ vocabulary.